2009
DOI: 10.1021/es900432m
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Detection of Naegleria Fowleri in Water Distribution Pipeline Biofilms and Drinking Water Samples

Abstract: Rapid detection of pathogenic Naegleria fowler in water distribution networks is critical for water utilities. Current detection methods rely on sampling drinking water followed by culturing and molecular identification of purified strains. This culture-based method takes an extended amount of time (days), detects both nonpathogenic and pathogenic species, and does not account for N. fowleri cells associated with pipe wall biofilms. In this study, a total DNA extraction technique coupled with a real-time PCR m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
81
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(83 citation statements)
references
References 33 publications
2
81
0
Order By: Relevance
“…This assay could easily be adapted to DNA extracted from the CSF and may be useful in identifying the causal species of a Naegleria infection. A recently developed real-time PCR assay is also available for the detection of N. fowleri (370,458). Naegleria may also be cultured from fresh CSF onto nonnutrient agar or various other medium formulations for further characterization (97,312).…”
Section: Naegleria Fowlerimentioning
confidence: 99%
“…This assay could easily be adapted to DNA extracted from the CSF and may be useful in identifying the causal species of a Naegleria infection. A recently developed real-time PCR assay is also available for the detection of N. fowleri (370,458). Naegleria may also be cultured from fresh CSF onto nonnutrient agar or various other medium formulations for further characterization (97,312).…”
Section: Naegleria Fowlerimentioning
confidence: 99%
“…The method cultures different volumes (usually serial dilutions) in 3–5 replicates each, consuming a lot of supplies and analyst time for reading all the plates, as well as requiring very specialized expertise. Since most species of Naegleria are morphologically indistinguishable, molecular methods are becoming rapidly more common as a means of detecting its presence [7, 10, 1820]. …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have described qPCR methodologies for the quantification of N. fowleri in water solely using cultured amebas under laboratory controlled conditions [21, 22]. In one study, the method was applied to a small sample set ( n = 6) of drinking water distribution biofilms and water [20], and only one study has reported application of qPCR to naturally occurring N. fowleri in surface water [19]. Environmental application data are important because qPCR is susceptible to inhibitors found in water samples, particularly concentrated water samples.…”
Section: Introductionmentioning
confidence: 99%
“…In 2007, investigation of the national outbreak found a multipurpose contact lens cleaning solution that has been associated with this illness ) while behavior and environmental factors such as overnight wear, trauma to the cornea, exposure to lake water and tap water have also been implicated in previous outbreaks and sporadic cases (Stehr-Green et al 1989;Seal et al 1992). Although the presence of Naegleria has been studied in water mains in Australia (Puzon et al 2009) and in well water in Arizona (Blair et al 2008;Bright et al 2009), Acanthamoeba presence in US water main systems has not been well defined. Knowledge of the extent to which pathogenic amoebae occur in US household water sources can provide theoretical clues to etiologies of amoeba-associated illnesses and suggest a focus for prevention measures.…”
Section: Introductionmentioning
confidence: 99%